Gardening and its effect on well-being and pro-environmental behaviours – a case study - Leong, Weng Kou (Nanyang Technological University, 2024)
Previous research has established that participating in gardening activities contributes towards regulating people’s mental health, building mental resilience, and stress management. Gardening has been shown to increase one’s connection with nature, which in turn, positively correlated with pro-environmental attitudes and behaviours. This current case study aims to understand the effects of gardening on participants’ connectedness to nature, well-being, and pro-environmental attitudes and behaviours. Employing an intervention model, nine undergraduate students participated in a gardening program lasting between five to eight weeks, cultivating kangkong (Ipomoea aquatica) from seed to harvest. Quantitative analysis of measures such as the Connectedness to Nature Scale and Nature Relatedness Scale found a significant positive correlation between participants' engagement in gardening and their sense of connectedness with nature. Results also showed a significant increase in pro-environmental attitudes and behaviours, as evidenced by the Environmental Motives Scale, and subjective well-being measured by the World Health Organisation Well-Being Scale. Qualitative exploration through nature journaling and semi-structured interviews revealed three key narratives: (a) gardening as a unifying force between people and nature, (b) the therapeutic benefits of gardening, and (c) a sense of responsibility and care for nature. In conclusion, I found that gardening increases participants’ levels of connectedness with nature and increases subjective well-being. It was also found that gardening increased pro-environmental attitudes and behaviours. The results advocate for the integration of gardening practices in urban living to foster individuals' connection with nature, well-being, and pro-environmental behaviours.